Carvedilol monotherapy and lifestyle modification among young patients with arterial hypertension and overweight/obesity in primary healthcare settings - G. I. Nechaeva; E. N. Loginova; M. I. Shupina; Yu. V. Tereshchenko (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To evaluate the dynamics of cardiovascular risk factors (RFs) and quality of life (QoL) in young patients with Stage I-II arterial hypertension (AH) and overweight/obesity during pharmaceutical (carvedilol monotherapy) and non-pharmaceutical (School for AH Patient) intervention. Material and methods. This open, randomised, clinico-preventive study in parallel groups included 63 out-patients with Stage I-II AH and overweight/obesity. The patients aged 18-27 years were randomised into 2 groups. All participants were randomised into two groups and received carvedilol (25 mg/d). In patients with uncontrolled blood pressure (BP), carvedilol dose could be titrated up to 50 mg/d. In addition, the main group (MG; n=32) received non-pharmaceutical structured intervention “School for AH Patient”. At baseline and after 24 weeks of the therapy, the levels of BP, QoL, body mass index (BMI), biochemical parameters, and RFs were assessed. Results. In the MG, RF levels were reduced to a greater extent than in the comparison group (CG). The MG patients demonstrated a greater decline in BMI (from 32,5±0,4 to 26,4±0,7 kg/m2 ; p<0,01) than the CG individuals (from 31,8±0,8 to 28,9±1,18 kg/m2 ; p<0,05). In the MG, baseline systolic and diastolic BP levels decreased by 20,1% and 25,6%, respectively; the respective decrease in the CG was 18,9% and 26%. In contrast to the CG, the MG demonstrated a significant improvement in QoL scales for physical functioning (р=0,003) and pain (р=0,032), with subsequent improvement in summary score of physical health component (р=0,001). Conclusion. In young AH patients with overweight/obesity, pharmacotherapy (carvedilol) should be combined with educational programs.